1990
DOI: 10.1093/ptj/70.10.611
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Curvature in Standing and Sitting in Two Types of Chairs: Relationship of Hamstring and Hip Flexor Muscle Length

Abstract: A purpose of this study was to determine the difference in the lumbar curves of subjects while they stood compared with while they sat in two chairs with different seat angles--the Balans Multi-Chair (BMC) and a standard conventional chair (SCC). An additional purpose was to determine the relationship between lumbar curvature and 1) anthropometric factors and hamstring and hip flexor muscle length during standing and during sitting in the two chairs and 2) amount of time spent sitting. Sixty-one men between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…Previous studies have demonstrated that individuals with relatively short hamstrings tend to exhibit greater posterior pelvic tilt (Bridger et al, 1992) and greater lumbar flexion (Stokes & Abery 1980;Bridger et al, 1989;Bridger et al, 1992) when seated. Conversely, in their study examining whether relationships existed between hamstring muscle length of males and their lumbar postures while sitting on "conventional" and "kneeling" chairs, Link et al (1990) did not find an association between these variables. They attributed the lack of an association found to the ineffectiveness of hamstring muscle action while knees of study participants were flexed.…”
Section: Integration Of Results With Previous Researchmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies have demonstrated that individuals with relatively short hamstrings tend to exhibit greater posterior pelvic tilt (Bridger et al, 1992) and greater lumbar flexion (Stokes & Abery 1980;Bridger et al, 1989;Bridger et al, 1992) when seated. Conversely, in their study examining whether relationships existed between hamstring muscle length of males and their lumbar postures while sitting on "conventional" and "kneeling" chairs, Link et al (1990) did not find an association between these variables. They attributed the lack of an association found to the ineffectiveness of hamstring muscle action while knees of study participants were flexed.…”
Section: Integration Of Results With Previous Researchmentioning
confidence: 88%
“…However, Stokes and Abery (1980) observed that individuals with the shortest hamstrings exhibited greater lumbar flexion even when knee angles were similar to those in office chair sitting (enclosed angle between thigh and leg ~ 90 degrees); extending the knees by 45 degrees had no additional effect on the sitting lumbar curvature in those who exhibited the least hamstring flexibility. Perhaps if Link et al (1990) had included females in their study or if other sitting conditions were examined, consistent relationships between hamstring flexibility and lumbar curvature during sitting would have surfaced. Although it Fig.…”
Section: Integration Of Results With Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…14,25,37 The subject was positioned supine on an examination table. The lower extremity not being tested was positioned in hip and knee extension.…”
Section: Indirect Measurements Of Hmlmentioning
confidence: 99%
“…14,16, 25 Chan et al 7 combined PA values of HML for men and women, whereas Krabak et al 23 studied only 15 subjects (10 men and 5 women). The defined end point of terminal knee extension varied among investigators, as did HML values.…”
mentioning
confidence: 99%